2014
DOI: 10.5194/acp-14-9213-2014
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of mineral dust long-wave radiative forcing: sensitivity study to particle properties and application to real cases in the region of Barcelona

Abstract: Abstract. The aerosol radiative effect in the long-wave (LW) spectral range is sometimes not taken into account in atmospheric aerosol forcing studies at local scale because the LW aerosol effect is assumed to be negligible. At regional and global scale this effect is partially taken into account: aerosol absorption is taken into account but scattering is still neglected. However, aerosols with strong absorbing and scattering properties in the LW region, like mineral dust, can have a non-negligible radiative e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
120
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(148 citation statements)
references
References 82 publications
(131 reference statements)
27
120
1
Order By: Relevance
“…LW scattering has a stronger impact on LW F TOA than on F A and RMSE is 2.9 W m −2 and 0.1 W m −2 , respectively, between P and PA experiments. Similar results have been reported by Dufresne et al (2002) and Sicard et al (2014). The number of large particles in the size distribution might be potentially underestimated by Aeronet, and thus the impact of LW scattering could be underestimated.…”
Section: Solar Villagesupporting
confidence: 77%
“…LW scattering has a stronger impact on LW F TOA than on F A and RMSE is 2.9 W m −2 and 0.1 W m −2 , respectively, between P and PA experiments. Similar results have been reported by Dufresne et al (2002) and Sicard et al (2014). The number of large particles in the size distribution might be potentially underestimated by Aeronet, and thus the impact of LW scattering could be underestimated.…”
Section: Solar Villagesupporting
confidence: 77%
“…In the longwave (LW) spectral range, the aerosol radiative properties are usually estimated theoretically with a Mie code. The variable that contains the absorption and scattering quantities, the extinction coefficient, is normalized to the extinction coefficient in the shortwave (SW) spectral range, most of the time in the visible spectral range [Dufresne et al, 2002;Sicard et al, 2014], or to the number concentration [Sokolik et al, 1998]. As measurements of the extinction coefficient or its integral, the aerosol optical depth (AOD), are available in the SW spectral range, the equivalent extinction coefficient or AOD in the LW spectral range can be deduced thanks to that theoretical normalized extinction coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the signs of the DREs vary between the SW and LW spectrum (Osborne et al, 2011) as well as within the Earthatmosphere system. More specifically, due to the attenuation (through scattering and absorption) of the SW radiation, dust aerosols warm the atmosphere and cool the surface (Huang et al, 2014), while reverse tendencies are revealed at longer wavelengths attributed to the absorption and re-emission of LW radiation by the mineral particles (Sicard et al, 2014a). Between the two spectrum ranges, the SW DREs are larger compared to the LW ones, in absolute terms, thus explaining their predominance when the corresponding calculations are made for the NET (SW + LW) radiation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Di Sarra et al, 2008;. Thus, a number of studies focused on Mediterranean dust outbreaks' impacts on the SW (Meloni et al, 2004;Gómez-Amoet al, 2011;Antón et al, 2012;Di Sarra et al, 2013;Obregón et al, 2015), LW (Antón et al, 2014;Sicard et al, 2014a) and NET Romano et al, 2016) radiation. However, the obtained results were representative at a local scale and, considering the high spatial variability of desert dust outbreaks, the optimum solution of assessing in a comprehensive way their impacts on weather and climate is provided by atmospheric-dust models.…”
Section: Introductionmentioning
confidence: 99%